The association between caries and childhood lead exposure. - Campbell, J R (2000)
Epidemiologic studies suggest an association between lead exposure and caries. Our objective was to establish whether children with a higher lead exposure as toddlers had more caries at school age than children with a lower lead exposure. We used a retrospective cohort design. A sample of children who attended second and fifth grades in the Rochester, New York, public schools during the 1995-1996 and 1996-1997 school years were examined for caries through a dental screening program. For each child we assessed the number of decayed, missing, or filled surfaces on permanent teeth (DMFS), and the number of decayed or filled surfaces on deciduous teeth (dfs); the number of surfaces at risk (SAR) was also recorded. Lead exposure was defined as the mean of all blood lead levels collected between 18 and 37 months of age by fingerstick [provided the blood lead level was [less than/equal to] 10 microg/dL)] or venipuncture. A total of 248 children (197 second graders and 51 fifth graders) were examined for caries and had a record of blood lead levels to define lead exposure. The mean dfs was 3.4 (range 0-29); the mean DMFS was 0.5 (range 0-8). Logistic regression was used to examine the association between the proportion of children with DMFS [Greater/equal to] 1, and the proportion with dfs [Greater/equal to] 1, and lead exposure [< 0.48 micromol/L vs. [Greater/equal to] 0.48 micromol/L (< 10 microg/dL vs. [Greater/equal to] 10 microg/dL)] while controlling for SAR, age at examination, and grade in school. For DMFS, the adjusted odds ratio was 0.95 [95% confidence interval (CI), 0.43-2.09; p = 0.89); for dfs, the odds ratio was 1.77 (95% CI, 0.97-3.24; p = 0.07). This study did not demonstrate that lead exposure > 10 microg/dL as a toddler was a strong predictor of caries among school-age children. However, the results should be interpreted cautiously because of limitations in the assessment of lead exposure and limited statistical power.